Analysis of the Influence of Service Quality on Customer Loyalty and Retention: Case Study on Tokopedia Services or Multinational Companies - Darmawan Hidayatullah, Galih; Edwin Syah, Muhammad (Journal of Management, 2025)
This study aims to analyze the role of Service Quality in increasing Customer Loyalty and Customer Retention at Tokopedia. The method used in this study is structural analysis of the model using PLS SEM to test the relationship between variables, as well as a comparison of predictions using RMSE and MAE between the two models. The results of the study indicate that Service Quality has a significant effect on Customer Loyalty (path coefficient = 0.969) and Customer Retention (path coefficient = 0.652). Customer Loyalty also functions as a mediator that strengthens the relationship between Service Quality and Customer Retention with a path coefficient of 0.827. In addition, the PLS SEM model showed better performance compared to the LM model, with lower RMSE and MAE values ​​for most of the indicators tested. These findings indicate that Service Quality is an important factor that can increase Customer Loyalty and Retention, and indicate that PLS SEM is more effective in predicting the relationship between variables compared to LM. This study provides practical implications for Tokopedia to improve service quality in an effort to retain customers and strengthen their loyalty..